Reactivation of nonsense-mediated mRNA decay protects against C9orf72 dipeptide-repeat neurotoxicity. - Xu, W.; Bao, P.; Jiang, X.; Wang, H.; Qin, M.; Wang, R.; Wang, T.; Yang, Y.; Lorenzini, I.; Liao, L.; Sattler, R.; Xu, J. (Brain : a journal of neurology, 2019)
Amyotrophic lateral sclerosis is a deleterious neurodegenerative disease without effective treatment options. Recent studies have indicated the involvement of the dysregulation of RNA metabolism in the pathogenesis of amyotrophic lateral sclerosis. Among the various RNA regulatory machineries, nonsense-mediated mRNA decay (NMD) is a stress responsive cellular surveillance system that degrades selected mRNA substrates to prevent the translation of defective or harmful proteins. Whether this pathway is affected in neurodegenerative diseases is unclear. Here we report the inhibition of NMD by arginine-rich dipeptide repeats derived from C9orf72 hexanucleotide repeat expansion, the most common cause of familial amyotrophic lateral sclerosis. Bioinformatic analysis of multiple transcriptome profiles revealed significant overlap of upregulated genes in NMD-defective cells with those in the brain tissues, micro-dissected motor neurons, or induced pluripotent stem cell-derived motor neurons specifically from amyotrophic lateral sclerosis patients carrying C9orf72 hexanucleotide repeat expansion, suggesting the suppression of NMD pathway in these patients. Using Drosophila as a model, we have validated that the C9orf72 hexanucleotide repeat expansion products could lead to the accumulation of the NMD substrates and identified arginine-rich dipeptide repeats, including poly glycine-arginine and poly proline-arginine, as the main culprits of NMD inhibition. Furthermore, in human SH-SY5Y neuroblastoma cells and in mouse brains, expression of glycine-arginine with 36 repeats (GR36) was sufficient to cause NMD inhibition. In cells expressing GR36, stress granule accumulation was accompanied by decreased processing body formation, which contributed to the inhibition of NMD. Remarkably, expression of UPF1, a core gene in the NMD pathway, efficiently blocked neurotoxicity caused by arginine-rich dipeptide repeats in both cellular and Drosophila models. Although not as effective as UPF1, expression of another NMD gene UPF2 also ameliorated the degenerative phenotypes in dipeptide repeat-expressing flies, indicating that genetically reactivating the NMD pathway could suppress dipeptide repeat toxicity. Finally, after validating tranilast as an NMD-activating drug, we demonstrated the therapeutic potential of this asthma drug in cellular and Drosophila models of C9orf72 dipeptide repeat neurotoxicity. Therefore, our study has revealed a cellular mechanism whereby arginine-rich C9orf72 dipeptide repeats could inhibit NMD activities by reducing the abundance of processing bodies. Furthermore, our results suggested that activation of the NMD pathway could be a potential therapeutic strategy for amyotrophic lateral sclerosis with defective RNA metabolism.